Germline mutations in BRCA1 and BRCA2 in epithelial ovarian cancer patients in Brazil. Issue 1 (December 2016) - Maistro, Simone; Teixeira, Natalia; Encinas, Giselly; Katayama, Maria; Niewiadonski, Vivian; Cabral, Larissa; Ribeiro, Roberto; Gaburo Junior, Nelson; de Gouvêa, Ana; Carraro, Dirce; Sabino, Ester; Diz, Maria; et al.
Abstract Background Approximately 8–15% epithelial ovarian cancer patients areBRCA1 orBRCA2 germline mutation carriers. Brazilian inhabitants may have peculiar genetic characteristics associated with ethnic diversity, and studies focusing on the entireBRCA1/BRCA2 gene sequencing in Brazilian ovarian cancer patients are still lacking. The aim of this study was to evaluateBRCA1/2 mutations, through entire gene sequencing, in a Brazilian population of women with epithelial ovarian cancer. Methods In a cross sectional study performed in one reference centre for cancer treatment in São Paulo, Brazil, 100 patients diagnosed with epithelial ovarian cancer unselected for family history of breast and/or ovarian cancer were included. The complete coding sequence ofBRCA1 /2 genes was evaluated through Next-Generation or capillary sequencing. Large deletions were investigated through Multiplex Ligation-dependent Probe Amplification (MLPA). Results Nineteen pathogenic mutations (BRCA1 :n  = 17 andBRCA2 :n  = 2) featuring 14 different mutations, including two large deletions inBRCA1 (exon 1–2 deleted and exon 5–7 deleted) were identified. Three mutations were detected more than once (c.3331_3334delCAAG, c.5266dupC and c.4484G > T). Two novel frameshift mutations were identified, one inBRCA1 (c.961_962delTG) and one inBRCA2 (c.1963_1963delC).BRCA1/2 mutations were seen in 35.5% of the patients with first and/or second-degree relatives with breast and/or ovarian cancer. Nineteen variants of uncertain significance (VUS) were detected (BRCA1 :n  = 2 andBRCA2 :n  = 17), including five distinct missense variants (BRCA1 : c.5348 T > C;BRCA2 : c.2350A > G, c.3515C > T, c.7534C > T, and c.8351G > A). Conclusions Among epithelial ovarian cancer patients unselected for family history of cancer, 19% wereBRCA1/2 germline mutation carriers. Almost ¾ of theBRCA mutations, including two large deletions, were detected only once. Our work emphasizes the need of entire gene sequencing and MLPA screening in Brazil.